EFEKTIVITAS SEMANTIK PRIMING DALAM ATASI FENOMENA TIP OF THE TONGUE - Ira Septira Dewi; Hairus Salikin (Universitas Muhammadiyah Surakarta, 2022)
The obstacle in accessing words that have been stored in memory is called the Tip of the Tongue phenomenon (ToT). This study aimed to measure the effectiveness of semantic priming techniques and sub lexicon codes in facilitating the process of accessing the lexicon when the subjects are in ToT state. This research is a qualitative descriptive study where the researcher conducted an experiment with a psycholinguistic analysis approach. The data are in the form of target words, prime words, and the success rate of the subject in recalling words. The data were obtained from the experiments, interviews, and observations involving 8 students at the tertiary level with an age range of 18-22 years. The results showed that the effectiveness rate of semantic priming in the process of accessing the lexicon is 67,6%, onset 8,9%, first syllable 23,5%. In addition, there were also factors that influenced the subjects' success in recalling words, such as age, character and intelligence, subject selective processes, inhibiting words, health and word acquisition processes. To conclude, priming associative semantics was quite effective in helping the subject recall words when the subject in the Tip of the Tongue State.